The impact of sharing economy platforms, management accounting systems, and demographic factors on financial performance: Exploring the role of formal and informal education in MSMEs - Diana Zuhroh; Johnny Jermias; Sri Langgeng Ratnasari; Sriyono; Elok Nurjanah; Mochammad Fahlevi (Journal of Open Innovation: Technology, Market and Complexity)
This study analyzes the effectiveness of sharing economy platforms and management accounting systems (MAS) on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Malang City, Indonesia, by considering the moderating effect of demographic factors such as gender, age, and business tenure. The investigation also examines the impact of formal and informal education on financial performance, positing that practical training yields greater financial improvement than theoretical schooling. This research examines 234 MSMEs using structural equation modeling (SEM) with SmartPLS and employs path analysis to investigate the impact of sharing economy platforms on MAS, as well as its consequences for financial performance. The results indicate that sharing economy platforms and MAS have a significant effect on financial performance. Informal education has a significant effect on sharing economy platforms and MAS, whereas formal education has a negative effect on financial performance. Demographic factors were observed to have a significant moderating effect on the path from MAS to financial performance. This study introduces the Adaptive Financial Capability Model (AFCM), a novel framework that uniquely integrates adaptive learning derived from informal education with demographic factors. By bridging practical training with contextual variables, such as gender, age, and business tenure, the AFCM provides an original perspective on enhancing financial management and technology adoption within MSMEs.